2006
DOI: 10.1515/jpm.2006.058
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of the autonomic nervous system: differences in heart rate variability in premature vs. term infants

Abstract: Maturation of the ANS is accompanied by increasing HRV with a pronounced increase of parasympathetic activity. These changes are measurable by short-term recordings. The physiological pulses concerning baroreceptor reflex activity and respiratory modulation were similar in prematures and term infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
92
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(104 citation statements)
references
References 23 publications
9
92
1
2
Order By: Relevance
“…It is also associated with poor long-term neurodevelopmental outcome [9][10][11][12]. In our study, the extent of injury (i.e., number of regions) did not show significant direct correlation with HRV, and yet the location of injury did.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…It is also associated with poor long-term neurodevelopmental outcome [9][10][11][12]. In our study, the extent of injury (i.e., number of regions) did not show significant direct correlation with HRV, and yet the location of injury did.…”
Section: Discussioncontrasting
confidence: 72%
“…In the newborn, several studies have demonstrated that decreased HRV is an indicator of ANS dysfunction and is linked to poor short-term outcome measures such as neonatal survival and the rate of neonatal complications [5,[8][9][10]. It is also associated with poor long-term neurodevelopmental outcome [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the first steps is peripheral vasoconstriction [20] which was found diminished or abolished in very low birth weight infants during the first days of life [15,18,20,23] , but returns to normal with increasing chronological age [20,23,24] . In contrast to the parasympathetic system [20,21] , the sympathetic system, mainly responsible for vasomotor control, develops slower [11,20] . This could be one of the explanations where a large body area, such as the head in this case was found to warm-up during SSC (Figures 3 and 4), but failed to keep its temperature in I2.…”
Section: Discussionmentioning
confidence: 99%
“…That is, the authors of only two studies examined late preterm population and only one examined newborns >30 weeks gestation. It has been documented that there are several variables which contribute to physiological variation in vital signs such as gestation age, 30,45,50 sex, 16,18 vital signs, [15][16][17][18][19][20][21][22][23][24] and activity. 16,29,51 This suggests that a universal reference range for newborns is problematic, as it does not reflect the complex interplay of variables that impact on clinical wellbeing.…”
mentioning
confidence: 99%